A refined diffuse cohesive approach for the failure analysis in quasibrittle materials—part II: Application to plain and reinforced concrete structures. Issue 12 (28th August 2019) - De Maio, Umberto; Greco, Fabrizio; Leonetti, Lorenzo; Luciano, Raimondo; Nevone Blasi, Paolo; Vantadori, Sabrina
Abstract: This work presents the numerical application of the diffuse cohesive interface model introduced in the Part I paper to the failure analysis of plain and reinforced concrete structures, subjected to complex loading conditions, inducing mixed‐mode fracture initiation and propagation. With the aim of capturing the interaction between concrete and steel reinforcements, the adopted fracture model is incorporated in a novel, more general numerical framework for the nonlinear analysis of reinforced concrete structures. Such a framework includes a newly proposed embedded truss model for the reinforcing bars, allowing them to be crossed by the neighboring propagating cracks. Comparisons with available experimental results are provided, assessing the reliability and the numerical accuracy of the proposed concrete model, with reference to plain specimens subjected to single‐crack propagation as well as to reinforced elements subjected to multiple cracking. Highlights: An integrated fracture model is proposed to simulate failure in concrete structures Interaction between cracks and rebars is accounted for via an embedded truss model Mesh dependency and mode‐II cohesive parameter sensitivity issues are investigated Comparisons with experiments assess the reliable application to RC structures